2003
DOI: 10.1093/ajcn/77.5.1287
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of foods enriched with plant- or marine-derived n−3 fatty acids on human immune function

Abstract: An intake of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
114
4
8

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(136 citation statements)
references
References 29 publications
10
114
4
8
Order By: Relevance
“…In healthy volunteers, increasing fish oil intake suppressed the in vitro synthesis of interleukin-2, interleukin1b, interleukin-1a, and tumor necrosis factor-a (Endres et al, 1989(Endres et al, , 1993. However, placebo-controlled studies found that fish oil does not affect ex vivo cytokine production (Blok et al, 1997) or the functional activity of neutrophils, monocytes, or lymphocytes in healthy humans (Kew et al, 2003). Few studies investigated effects of n-3 fatty acids on CRP.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy volunteers, increasing fish oil intake suppressed the in vitro synthesis of interleukin-2, interleukin1b, interleukin-1a, and tumor necrosis factor-a (Endres et al, 1989(Endres et al, , 1993. However, placebo-controlled studies found that fish oil does not affect ex vivo cytokine production (Blok et al, 1997) or the functional activity of neutrophils, monocytes, or lymphocytes in healthy humans (Kew et al, 2003). Few studies investigated effects of n-3 fatty acids on CRP.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma phospholipids may be a mechanism to transport PUFAs to cells and tissues, and their fatty acid composition reflects that of the membranes of some cells [154]. The effect of increased ALA intake on fatty acids in plasma phospholipids has been reported in several studies.…”
Section: Increased Intake Of Alpha-linolenic Acidmentioning
confidence: 99%
“…Increased consumption of ALA or SDA has been shown to increase the proportion of EPA and DPA in membranes of inflammatory cells such as neutrophils, monocytes and lymphocytes [38,99,107,128,130,133,[152][153][154]163] (Tables 7 and 8), indicating the potential of plant derived ω-3 PUFAs to reduce inflammation and to protect against chronic inflammatory diseases.…”
Section: Alpha-linolenic Acid Stearidonic Acid and Inflammationmentioning
confidence: 99%
“…Consequently, it could not be excluded that the increased incorporation of DHA in neutrophil lipids and the subsequent production of LT observed for each dose of DHA may also reflect the effect of cumulative doses of DHA. Results from human studies indeed indicate that the level of DHA reached a plateau after 18 weeks of dietary supplementation (18) and most of the published data reported longer supplementation periods (from 3 weeks to 6 months (5,6,8,9,13) ). However, the present data suggest that changes in total lipid content occurred within 2 weeks and therefore earlier than that reported until now.…”
Section: Discussionmentioning
confidence: 96%